An IEEE 802.21-based Approach to Integrate Unidirectional Wireless Technologies into QoS-constrained Broadband Wireless Mesh Access Networks. Issue 2 (June 2010) - Kretschmer, Mathias; Ghinea, Gheorghita
No abstract available